PERILAKU PENGUNJUNG OBJEK WISATA PANTAI PURUS DALAM MENJAGA KEBERSIHAN LINGKUNGAN PANTAI PURUS KELURAHAN PURUS KECAMATAN PADANG BARAT KOTA PADANG - NICO FERNANDO; Surtani surtani (JURNAL BUANA, 2021)
The study aims to identify the behavior of the visitor in maintaining the purus beach environment clean and the efforts of the visitor to maintain the purus bay environment .It is a descriptive study with a qualitative approach. The study is conducted at the purus coast tourist attraction western wilderness town. Research informants are visitors who are asked to submit information to the study. The type of data in this study is primary and secondary data. Data collection techniques in this study are done with observation, interviews, and documentation. Data analysis USES (1) data reduction, (2) data exposure, and (3) hypothetical withdrawal. The study resulted (1) in visitor behavior in the cleanliness of purus beach environments enough to ensure the coefficient of the purus coast environment. Researchers believe that much garbage is caused by traders who dispose of waste products in the local area. Researchers also see the awareness that the visitor has of garbage emanating from himself by refraining from littering out of trash (2) the attempts that the visitor gave to maintaining purus coast are less noticeable. Researchers have learned firsthand that efforts to clean up the beach environment are made by hauling out their own beverage and food - free garbage to the garbage. The lack of availability of refuse according to researchers has significantly affected beach cleanliness. With the limitation of a visitor's garbage can, it becomes a litany that he finds effective rather than a dumpster. The availability of trash bins in busy tourist resorts has to be increased so that there are no more excuses or visitors who discard garbage causing personal discomfort.